2005
DOI: 10.1177/104990910502200207
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory study on end-of-life issues: Barriers to palliative care and advance directives

Abstract: Of the 13 obstacle statements, results show that respondents rated the top three barriers as 1) physician reluctance to make referrals (mean = 4.23), 2) physician lack of familiarity with availability and suitability of hospice (mean = 3.93), and 3) association of hospice with death (mean = 3.93). There was a statistically significant difference in scores for respondents from hospitals and respondents from hospices on their assessment of barriers for the association of hospice with death (t = -2.09, p < .05) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 2 publications
1
48
0
1
Order By: Relevance
“…Many studies have been done regarding obstacles to hospice referral [3-6, 10, 13, 19, 21, 23, 29], and various barriers have been identified. They include the difficulty of predicting prognosis [3,29], lack of physician acceptance of terminal diagnosis and death [1,6,14], physician's unwillingness to refer to hospice service [1,5], physician's unfamiliarity with hospice [5], physician's negative opinion of hospice service [5], insufficient knowledge of physician about hospice service [1], insufficient education for physicians about palliative care [1,6,14], a medical system that does not include hospice as standard care [14,30], patient's and family's unwillingness to use hospice [1,19,23], patient's and family's desire for life-prolonging treatment [29], lack of acceptance of a terminal diagnosis by the patient and family [23,29,30], insufficient knowledge by the general population and patients and families about hospice service [10,13], and social attitudes toward death [30].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been done regarding obstacles to hospice referral [3-6, 10, 13, 19, 21, 23, 29], and various barriers have been identified. They include the difficulty of predicting prognosis [3,29], lack of physician acceptance of terminal diagnosis and death [1,6,14], physician's unwillingness to refer to hospice service [1,5], physician's unfamiliarity with hospice [5], physician's negative opinion of hospice service [5], insufficient knowledge of physician about hospice service [1], insufficient education for physicians about palliative care [1,6,14], a medical system that does not include hospice as standard care [14,30], patient's and family's unwillingness to use hospice [1,19,23], patient's and family's desire for life-prolonging treatment [29], lack of acceptance of a terminal diagnosis by the patient and family [23,29,30], insufficient knowledge by the general population and patients and families about hospice service [10,13], and social attitudes toward death [30].…”
Section: Introductionmentioning
confidence: 99%
“…(10,12,31,32) One finding showed that 28% of doctors and residents believed their own lack of knowledge about hospice services limited their referrals. (15) Doctors may indeed not have the skills, training or experience to recognise when referral to PC should occur and it has been shown that doctors undertaking training and professional development around end-of-life issues are more likely to practice earlier referral to PC.…”
Section: Patient and Family-related Issuesmentioning
confidence: 99%
“…Many clinicians had biased views about advance directives, and some perceived that patients and family members were reluctant to discuss these care issues. In addition, insufficient knowledge exists among clinicians regarding advance directives and end-of-life or hospice care, and most felt inadequately trained to deliver news, such as a cancer diagnosis or prognosis and recommending end-of-life care options (Badzek et al, 2006;Bradley et al, 2002;Cramer, McCorkle, Cherlin, JohnsonHurzeler, & Bradley, 2003;Duke & Thompson, 2007;Feeg & Elebiary, 2005;Jezewski, Brown, et al, 2005;Jezewski, Meeker, & Robillard, 2005;Lipson, Hausman, Higgins, & Burant, 2004;Morrison, Morrison, & Glickman, 1994;Scherer, Jezewski, Graves, Wu, & Bu, 2006).…”
Section: E401mentioning
confidence: 99%